(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
This article presents a direct method for calculating the normal form coefficients of a 1:1 resonant Hopf bifurcation in reaction-diffusion systems with time delay and Neumann boundary conditions. The formulas obtained in this paper can be easily implemented using a computer algebra system such as Maple or Mathematica.